2019
DOI: 10.3390/nano9030451
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Ge-DLC Nanocomposite Biomaterials Prepared by Laser Codeposition

Abstract: This paper deals with the synthesis and study of the properties of germanium-doped diamond-like carbon (DLC) films. For deposition of doped DLC films, hybrid laser technology was used. Using two deposition lasers, it was possible to arrange the dopant concentrations by varying the laser repetition rate. Doped films of Ge concentrations from 0 at.% to 12 at.% were prepared on Si (100) and fused silica (FS) substrates at room temperature. Film properties, such as growth rate, roughness, scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Hepatocytes are very specific cells: they are polarized, specialized, and species‐specific, making them uniquely susceptible to infections 37. Recently, we showed that among widely used hepatic cell lines, Huh7 is the most fragile cell line, which makes it ideal to assess acute toxicity of different substrates 31,38. Therefore, these cell lines were selected for the purpose of this work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hepatocytes are very specific cells: they are polarized, specialized, and species‐specific, making them uniquely susceptible to infections 37. Recently, we showed that among widely used hepatic cell lines, Huh7 is the most fragile cell line, which makes it ideal to assess acute toxicity of different substrates 31,38. Therefore, these cell lines were selected for the purpose of this work.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the cell seeding, all experimental substrates were sterilized by treatment with 70% ethanol for 20 min, followed by UV exposure for 1 h. For all cell experiments in this study, the cells were seeded on the sterilized substrates at an initial density of 25 000 cells cm –2 and were maintained under standard cell culture conditions (37 °C, 5% CO 2 ). Cells were allowed to grow on substrates for 4 days under standard cell culture conditions 38. When the cells were in the exponential growth phase, the monolayer was washed once in PBS and then stained by the addition of calcein AM (1 µM) and PI (50 µg mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For high quality confocal images, we used brand new high-resolution spinning disk confocal system IXplore SpinSR (Olympus) [54,59]. This technique was utilized to assess in great details the morphological changes of cells upon nanoparticle treatment.…”
Section: Confocal Microscopymentioning
confidence: 99%